Minimizing the Risk of Catastrophic Health Expenditure in China: A Multi-Dimensional Analysis of Vulnerable Groups - Wang, Jiahui; Tan, Xiao; Qi, Xinye; Zhang, Xin; Liu, Huan; Wang, Kexin; Jiang, Shengchao; Xu, Qiao; Meng, Nan; Chen, Peiwen; Li, Ye; Kang, Zheng; et al. (Frontiers in Public Health, 2021)
Background: In moving towards universal medical insurance in China, it is crucial to identify which populations should be prioritised for which interventions rather than blindly increasing welfare packages or capital investments. We identify the characteristics of vulnerable groups from multiple perspectives through estimating catastrophic health expenditure and recommend intervention priorities. Methods: Data were from National Health Service Survey conducted in 2003, 2008 and 2013. According to the WHO’s recommendation, this study adopted 40% as the CHE threshold. A binary regression was used to identify the determinants of CHE occurrence, a probit model was used to obtain CHE standardized incidence under the characteristics of single and two dimensions in 2013. Results: The total incidence of CHE in 2013 was 13.9%, which shows a general trend of growth from 2003 to 2013. Families in western and central regions and rural areas were more at risk. Factors related to social demography shows that households with a female or unmarried head of household and a low socioeconomic status were more likely to experience CHE. Households with older adults aged 60 and above had 1.524 times higher likelihood of experiencing CHE. Among the health insurance schemes, participants covered by the New Rural Cooperative Medical Scheme had the highest risk compared to participants of all basic health insurance schemes. Households with several members seeking out-patient, inpatient care or with non-communicable diseases were more likely to experience CHE. Households with members not seeing a doctor or hospitalized despite the need for it were more likely to experience CHE. Characteristics such as household head with the characteristics related to low socioeconomic status, having more than two hospitalized family members, ranked high. Meanwhile, the combination of having illiterate household heads and with being covered by other health insurance plans or by none ranked the first place. Cancer notably caused a relatively high medical expenditure among CHE households. Conclusion；In China, considering the vulnerability of population across different dimensions is conducive to the alleviation of high CHE. Furthermore, people with multiple vulnerabilities should be prioritized for intervention. Identifying and targeting them to offer help and support will be an effective approach.